2016
DOI: 10.1007/s10509-016-2801-5
|View full text |Cite
|
Sign up to set email alerts
|

Photometry of Centaurs and trans-Neptunian objects: 2060 Chiron (1977 UB), 10199 Chariklo (1997 CU26), 38628 Huya (2000 EB173), 28978 Ixion (2001 KX76), and 90482 Orcus (2004 DW)

Abstract: Both Centaurs and trans-Neptunian objects (TNOs) are minor bodies found in the outer Solar System. Centaurs are a transient population that moves between the orbits of Jupiter and Neptune, and they probably diffused out of the TNOs. TNOs move mainly beyond Neptune. Some of these objects display episodic cometary behaviour; a few percent of them are known to host binary companions. Here, we study the lightcurves of two Centaurs -2060 Chiron (1977 periodogram analysis of the light-curves of these objects gives … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Using the absolute magnitude H V = 3.774 ± 0.021 measured by Alvarez-Candal et al (2016) gives a geometric albedo p V = 0.108 ± 0.002. Galiazzo et al (2016) found that Ixion has a rotation period of 12.4 ± 0.3 hr with a low-amplitude (<0.1 mag) rotation curve. Prior to that observation, Rousselot & Petit (2010) measured Ixion's rotation curve with a period 15.9 ± 0.5 hr and amplitude 0.06 ± 0.03 mag (Table 3).…”
Section: Large Classical Kbo (50000) Quaoarmentioning
confidence: 96%
“…Using the absolute magnitude H V = 3.774 ± 0.021 measured by Alvarez-Candal et al (2016) gives a geometric albedo p V = 0.108 ± 0.002. Galiazzo et al (2016) found that Ixion has a rotation period of 12.4 ± 0.3 hr with a low-amplitude (<0.1 mag) rotation curve. Prior to that observation, Rousselot & Petit (2010) measured Ixion's rotation curve with a period 15.9 ± 0.5 hr and amplitude 0.06 ± 0.03 mag (Table 3).…”
Section: Large Classical Kbo (50000) Quaoarmentioning
confidence: 96%
“…It orbits primarily between Saturn and Uranus, ranging from approximately 8.5 to 19 au, with orbital eccentricity of 0.38 and inclination of 7º. Its rotational period has been reported as 5.92 h (with low error, Marcialis & Buratti 1993), although a slightly shorter rotation of approximately 5.5 h was reported in more recent, sparsely-sampled data (Fornasier et al 2013, Galiazzo et al 2016. Upon discovery, Chiron was thought to be an asteroid, but it has since exhibited outbursting behaviour and is co-designated as comet 95P/Chiron (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…There was no detection of the light curve amplitudes obtained in 1997 and 1999 (Davies et al 1998;Peixinho et al 2001), when Chariklo was close to its maximum opening angle. Peak-to-peak amplitudes of 0.13 mag and 0.11 mag were then measured in 2006 and 2013, respectively (Galiazzo et al 2016;Fornasier et al 2014). As not given by the authors, we adopt conservative upper limits for the amplitudes in 1997 and 1999, and uncertainties for those of 2006 and 2013, derived from the uncertainties in the respective photometry.…”
Section: Analysis Of Photometrymentioning
confidence: 99%
“…Rotational light curves obtained in the visible between 1997 and 2013 exhibit a variable peak-to-peak amplitude from non detectable in 1997 and 1999 to amplitudes of 0.11-0.13 in 2006 and 2013 respectively (Davies et al 1998;Peixinho et al 2001;Fornasier et al 2014;Galiazzo et al 2016). This can be produced by an elongated body, longitudinal albedo variegations or, more probably, a combination of both.…”
Section: Introductionmentioning
confidence: 99%